Correction: Development of UV spectrophotometry methods for concurrent quantification of amlodipine and celecoxib by manipulation of ratio spectra in pure and pharmaceutical formulation. - Mahesh Attimarad; Katharigatta Narayanaswamy Venugopala; Bandar Essa Aldhubaib; Nagaraja SreeHarsha; Anroop Balachandran Nair (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0222526.].